ENTREPRENEURSHIP SPIRIT IN THE DIGITAL ERA : HOW THE ROLE OF ATTITUDES, EDUCATION AND ENVIRONMENT - Heri Erlangga; Iyus Rustandi; yusuf arifin; Farid Riadi; Ida Hindarsah (Jurnal Manajemen Industri dan Logistik, 2021)
This research was conducted with the aim of knowing the effect of attitude on interest in entrepreneurship, influence of education on interest in entrepreneurship, influence of environment on interest in entrepreneurship. The population of this research is students of a private university in Banten. Data were collected by simple random sampling of 230 students, data obtained by distributing online questionnaires, data analysis using Structural Equation Modeling SmartPLS 3.0 analysis. Stages of testing the quality of data from the use of research instruments are evaluated using validity and reliability tests and hypothesis testing. Interest in entrepreneurship has a positive value, meaning that the educational variable has a positive influence on interest in entrepreneurship. Based on the conclusions above, some suggestions that can be given are: It is necessary to conduct entrepreneurship training in order to increase the growth of the entrepreneurial spirit. There is a need for special guidance for people who already have a business or who are just about to set up a business, both from the relevant agencies and universities.